Boy erased : a memoir - Conley, Garrard (Riverhead Books, 2016)
"The son of a Baptist pastor and deeply embedded in church life in small-town Arkansas, Garrard Conley was terrified and conflicted about his sexuality as a young man. When Garrard was a nineteen-year-old college student, he was outed to his parents, and was forced to make a life-changing decision: either agree to attend a church-supported conversion therapy program that promised to "cure" him of homosexuality; or risk losing family, friends, and the God he had prayed to every day of his life. Through an institutionalized twelve-step program heavy on Bible study, he was supposed to emerge heterosexual, ex-gay, cleansed of impure urges and, because of his brush with sin, stronger in his faith in God. Instead, even when faced with a harrowing and brutal journey, Garrard found the strength and understanding to search for his true self, empathy, and forgiveness. By examining and excavating his buried past and the burden of a life lived in shadow, Garrard traces the complex relationships among family, faith, and community. At times heartbreaking, at times triumphant, this memoir is a testament to love that survives despite all odds."--Dust jacket.